1998
DOI: 10.21273/jashs.123.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Flowering, and Postharvest Performance of Single-stemmed Rose (Rosa hybrida L.) Plants in Response to Light Quantum Integral and Plant Population Density

Abstract: The cut rose, grown as a single-stemmed crop, resembles a potted plant and can be adapted to transportable bench systems. Potentially, this cultivation method could increase control of rose development, flexibility of production and produce, and automation of difficult or laborious cultural operations. Synchronous growth and flowering is considered important. The effects of increased quantum irradiation integral and plant density on shoot growth, fresh biomass production, and bloom quality were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
2
5
2
Order By: Relevance
“…PPFD level during propagation did not significantly affect shoot growth in this experiment. Thus, contrary to what has been indicated for cut rose (Moe, 1973;Bredmose, 1998), PPFD at 46 µmol m -2 s -1 during propagation as compared to 72 µmol m -2 s -1 was apparently sufficient for later shoot growth in 'Heidi' miniature rose plants. However, in cut rose 'Madelon' total plantlet dry weight was related to leaf area indicating a connection between irradiance during propagation and cutting growth (Costa and Challa, 2002).…”
Section: Shoot Growthcontrasting
confidence: 85%
See 2 more Smart Citations
“…PPFD level during propagation did not significantly affect shoot growth in this experiment. Thus, contrary to what has been indicated for cut rose (Moe, 1973;Bredmose, 1998), PPFD at 46 µmol m -2 s -1 during propagation as compared to 72 µmol m -2 s -1 was apparently sufficient for later shoot growth in 'Heidi' miniature rose plants. However, in cut rose 'Madelon' total plantlet dry weight was related to leaf area indicating a connection between irradiance during propagation and cutting growth (Costa and Challa, 2002).…”
Section: Shoot Growthcontrasting
confidence: 85%
“…Temperature optima for leaf photosynthesis and carbon export rate in cut rose 'Samantha' were both c 25°C (Jiao and Grodzinski, 1998). Though high PPFD could weaken inhibition and promote axillary bud growth in cut rose (Mor et al, 1980;Bredmose, 1998), this was not found in the present experiment, suggesting that a PPFD at 46 µmol m -2 s -1 was sufficient, or that 72 µmol m -2 s -1 was too low for further effect. The growth of axillary buds in extra short cuttings was delayed.…”
Section: Axillary Bud Growthcontrasting
confidence: 65%
See 1 more Smart Citation
“…Similar results were reported by Moe (1973) who described that rooting of 'Roswytha' rose cuttings was enhanced at increased irradiance. Bredmose (1998) also, reported an enhanced response resulting from increased photosynthetic photon flux density (PPFD) for rose cuttings. In 'Gouni', however, the optimum light intensity for rooting was 180 µmol m -2 s -1 .…”
Section: Research Reportmentioning
confidence: 99%
“…The uppermost, young leaf was used throughout the experimental period. As roses are generally cultivated over a range of 20–30°C for day temperature and 18–20°C for night temperature (Beeson 1990; Bredmose 1998; Gonzalez‐Real and Baille 2000; Jiao and Grodzinski 1998; Kim and Lieth 2003; Kool et al . 1996), we grew the assimilation shoots at two different day/night temperature regimes of 20/15°C and 30/25°C.…”
Section: Introductionmentioning
confidence: 99%